If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 7 + x = 3(x + -1) Reorder the terms: 7 + 4x + x = 3(x + -1) Combine like terms: 4x + x = 5x 7 + 5x = 3(x + -1) Reorder the terms: 7 + 5x = 3(-1 + x) 7 + 5x = (-1 * 3 + x * 3) 7 + 5x = (-3 + 3x) Solving 7 + 5x = -3 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 7 + 5x + -3x = -3 + 3x + -3x Combine like terms: 5x + -3x = 2x 7 + 2x = -3 + 3x + -3x Combine like terms: 3x + -3x = 0 7 + 2x = -3 + 0 7 + 2x = -3 Add '-7' to each side of the equation. 7 + -7 + 2x = -3 + -7 Combine like terms: 7 + -7 = 0 0 + 2x = -3 + -7 2x = -3 + -7 Combine like terms: -3 + -7 = -10 2x = -10 Divide each side by '2'. x = -5 Simplifying x = -5
| 36x+2=0 | | 10x-15=0 | | 49b^3-4b=0 | | 4y+2=6(8y-7) | | 17p+10+52q+13p-2q= | | 8-4(2-5x)-3(2x-3)=9+14x | | 2x-(5x+5)=3x-17 | | x/5+7=18 | | 15=-2(2T+1) | | 6y+2=3(3+2y) | | n-10+8n+3= | | 7x^2+7x-6=0 | | 3(1-2b)+5(7b-8)=50 | | 3a-1=14-2a | | 12(.25-1)=12 | | 5.44=0.34a | | (3z^2-2z-33)= | | x^2+16=1 | | 7r+7+1r= | | (4x+4)(5x+7)=0 | | 8-5(2-5x)-3(2x-3)=9+14x | | 45x^4+15x^6=0 | | -2p+4p= | | 8w-5= | | 2(4q-12)+39=6q+1 | | 2p+4p= | | 20y+1=71 | | 8c^2-18cd-5d^2= | | 3z^2-2z-33= | | 8n+10n= | | 4(x-1)-5=3x+7 | | 8-(4-x)=5+x |